THE EFFECT OF VARIOUS TYPES OF FERTILIZER ON THE GROWTH AND YIELD OF LONG BEAN PLANTS (VIGNA SINENSIS L.) - ilham, ilham; Suyono, Suyono; Sanjaya, Muhammad Fahyu; Ardiana, Ardiana (Journal of Agriculture, 2023)
Long beans are one type of vegetable hortcultural plant that is popular throughout the world which is widely used as food or daily consumption, produced to be used as seeds and used as medicines in the world of health. This study aims to determine the effect of applying various fertilizers on the growth and production of string bean plants. This research was conducted in Lembang Village, Banggae Timur District, Majene Regency, Sulawesi Barat Province. The treatment in this study was designed with a simple Group Randomized Design with 4 treatments and 4 repetitions, namely P0 = No Fertilizer (control), P1 = Leachate 5 ml, P2 = MOL 5 ml, P3 = NPK Fertilizer 5 ml. Leachate and MOL as liquid organic fertilizers dissolved in water and applied per week after planting. NPK fertilizer as an inorganic fertilizer that is thawed with water and applied per week after planting. The results showed that the treatment of various fertilizers (P0, P1, P2, and P3) did not have a real effect on the growth and production of string bean tama, especially on the number of fruits. while the application of leachate water fertilizer dose of 5 ml (P1) gave higher results on the height and number of leaves of long bean plants compared to without fertilizer (P0) and the application of MOL 5 ml (P2) and NPK dose 5 ml (P3). The effect of applying NPK 5 ml (P3) fertilizer on the growth of long bean plants only appears in the variable number of leaves.